Sustainable development in Sumatra Island: Spatial distribution and its implications - Optari, Leni Kurnia; Bina, Al (Priviet Social Sciences Journal, 2025)
This study aims to examine the implementation of sustainable development on Sumatra Island and its spatial distribution, assessed from economic, social, and environmental dimensions. Data analysis was conducted using a composite index method, which comprises various unitless indicators or sub-indicators. Furthermore, Geographic Information System (GIS) techniques were applied to identify the spatial distribution of sustainable development. For the economic dimension, indicators include Gross Regional Domestic Product (GRDP) per capita and the open unemployment rate. The social dimension was analyzed using the Human Development Index (HDI), school participation rates, life expectancy at birth, and poverty rates. Meanwhile, the environmental dimension utilized indicators such as the environmental quality index, air quality index, water quality index, and land cover quality index. Based on the composite index analysis of sustainable development in Sumatra from 2016 to 2020, the results indicate that regional development, in the short term, can be classified as moderately sustainable. Spatially, the sustainable development index values ranged from 50.01 to 75.00, which falls into the moderately sustainable category.